The Function of Twisted Gastrulation in Regulating Osteoclast Differentiation is Dependent on BMP Binding - Huntley, Raphael (J Cell Biochem, 2015)
Proper regulation of osteoclast (OCL) function is critical for normal bone homeostasis. Bone morphogenetic protein (BMP) signaling and its regulation have been shown to have direct effects on OCL differentiation and activity. One of the major modulators of BMP signaling in the extracellular space is the secreted protein twisted gastrulation (TWSG1), which can inhibit BMP signaling and OCL differentiation. In this study we examine specific N-terminal regions of TWSG1 protein that have been previously proposed as BMP binding sites to determine whether TWSG1 binding to BMPs is required for its inhibitory effects on OCLs. We demonstrate that overexpression of wild type TWSG1 suppresses osteoclastogenesis, while overexpression of mutant TWSG1 proteins (W66A and N80Q/N146Q mutants), which cannot bind BMPs, leads to increased BMP signaling, enhanced osteoclastogenesis, increased resorptive activity and expression of OCL-specific genes. Our results show that BMP binding is required for TWSG1-mediated inhibition of OCL formation and function, and validate the critical functional regions within the TWSG1 protein for these interactions.